KINERJA DIPENGARUHI OLEH KEPEMIMPINAN MELALUI MOTIVASI KARYAWAN PT. CIBUBUR INDAH MOTOR/HONDA CIBUBUR - Eddy Sanusi Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
To find out employee performance is influenced by leadership throughemployees motivation of PT. Cibubur Indah Motor/Honda Cibubur. This research was conducted on employees of PT. Cibubur Indah Motor (Honda Cibubur). The data collection method used is by distributing closed questionnaires. In this study, researchers used a saturated sample method where samples were used from all members of the population. For data analysis models researchers use path analysis tests. The results showed that leadership has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Leadership has a positive and significant effect on motivation. And leadership affects employee performance through motivation at PT Cibubur Indah Motor (Honda Cibubur).